THE EFFECT OF SPIRITUAL COPING STRATEGY EDUCATION ON REDUCING ANXIETY LEVELS AMONG PREOPERATIVE ORTHOPEDIC PATIENTS AT RSUD PANEMBAHAN SENOPATI BANTUL - Clara Marsanda Putri Monoarfa Clara; Vita Purnamasari; Endah Tri Wulandari (Keperawatan Anestesiologi Program Sarjana Terapan, 2026)
Background: The high prevalence of anxiety among pre-operative orthopedic at RSUD Panembahan Senopati Bantul indicates that available interventions have not fully addressed patients’ spiritual needs. Therefoe spiritual coping strategy education is required as a non-pharmacological approach to help reduce patient anxiety prior to surgery Objective: To determine the effect of spiritual coping strategy education on reducing anxiety levels in pre-operative orthopedic patients at RSUD Panembahan Senopati Bantul Methods: A quantitative study with a quasi-experimental pretest-posttest with control group design. The sample consisted 62 respondents selected through purposive sampling. Instruments used included the APAIS quistionnaire, (SOP). Data were analyzed using Wilcoxon test and Mann-Whitney test Results: Prior to intervention, the majority of respondents in both groups experienced moderate anxiety. Following the spiritual coping strategy education, the intervention group showed a significant reduction in anxiety levels. The Wilcoxon test revealed Sig. (2-tailed) <0,001 for the interventions group and Sig. (2-tailed) 0,004 for the control group. The Mann-Whitney test vielded p<0,001, indicating a significant difference between the group that received direct education and the group that only received leaflats Conclusion: Spiritual coping strategy education was proven in reducing anxiety levels among pre-operative orthopedic patients at RSUD Panembahan Senopati Bantul, with 87,1% of respondents in the intervention group experiencing a reduction in anxiety from moderate to mild